The Oxford handbook of international law in armed conflict - Clapham, Andrew; Gaeta, Paola; Haeck, Tom; Priddy, Alice (Oxford : Oxford University Press, 2014)
Written by a team of distinguished and internationally renowned experts, this Oxford handbook gives an analytical overview of international law as it applies in armed conflicts. It draws on international humanitarian law, human rights law, and the law of neutrality to provide a comprehensive picture of the status of law in war.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: War (International law); Neutrality; Human rights; Law; International law